Knowledge, Perception and Practices Towards Covid-19 Among HCW - Mahabub Aalam, Iqra Khan, Kashif Javed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In underdeveloped nations like Pakistan, nosocomial infections are a leading cause of high morbidity and death. Nosocomial infections may be reduced with the use of standard precautions based on appropriate self-care practises, proper information, and a positive attitude. Objective: The objective of the study is to know about the knowledge, attitudes and practices of health care providers regarding infection control. Study Design: Cross-sectional Place and Duration: Mayo Hospital Lahore. Jan-2021-July 2021 Material and Method: We interviewed a total of 100 health-care professionals, including physicians, nurses, pathologists, and paramedics. A sampling procedure that was convenient was chosen. Following the receipt of informed permission, participants were asked to complete the questionnaires that had been developed to assess their knowledge, attitudes, and behaviors in the area to control infection. SPSS 21.0 version was used to analyzed data. Results: There were 65 (65%) men and 35 (35%) women among the total of 100 health-care personnel. Eighty-five percent of those polled have a basic understanding of how infectious diseases are spread, and ninety-four percent believe that transmission-based precautions are effective in preventing infection. However, ninety-six percent of those polled believe that personal protective equipment (PPE) and strict adherence to standard precautions are essential in preventing infection. Health care workers (HCWs) on average report a shortage of PPE and 90.6% of HCWs wash their hands before and after the process. 71% of healthcare workers used PPE, yet only 78% of those workers recapped needles after using them. Conclusion: We found in this study that there was a high level of general knowledge, attitude, and behaviors among the responding health-care practitioners.